STUDY OF GAS POTENCY BASED ON GRAVITY ANOMALY MODELING AND SEISMIC PROFILE ANALYSIS AT BANGGAI-SULA BASIN - Ediar Usman; Panuju Panuju (BULLETIN OF THE MARINE GEOLOGY, 2013)
Banggai-Sula Basin is one of the basins with character of the micro-continent derived from northern part of Australia. Some traces the migration in the central part of Papua are slate, schist, and gneiss, current movement is facilitated by the Sorong Fault, which runs from the northern part of Papua to eastern part of Sulawesi. Results of gravity anomaly model (2D and 3D), seepage distribution, seismic and fields existing of oil and gas production in the western part of the Banggai-Sula Basin obtained a new prospect area in the northern part of Peleng Island, western part of Banggai Island, southern part of Banggai-Taliabu Islands, western and eastern part of Sulabesi Island. The new prospect area is reflected in the centre with form of the low morphology on gravity model and prospect trap on seismic data in the western part of Tolo Bay. Results of chemical analysis on the source rock of Buya Formation on Tmax vs Hydrogen Index (Tmax vs HI) Diagram shows the type III kerogen quality and the Oxygen Index vs Hydrogen Index (OI vs HI) Diagram shows the gas prone Type II, so that giving the impression that this area has the potential to containing the gas. The quality of the gas is included in the category of immature to mature type. Key word : marine geology, gravity anomaly model, trap, source rock, hydrocarbon quality, Banggai-Sula Basin Cekungan Banggai-Sula merupakan salah satu cekungan dengan karakter mikro-kontinen yang berasal dari pecahan Australia bagian utara. Beberapa jejak migrasi terdapat di bagian tengah Papua berupa batuan slate, schist, dan gneiss, pergerakannya saat ini difasilitasi oleh Sesar Sorong yang membujur dari Papua bagian utara hingga bagian timur Sulawesi. Hasil pemodelan gaya berat (2D dan 3D), daerah rembesan, seismik dan keberadaan lapangan produksi migas di bagian barat Cekungan Banggai-Sula diperoleh hasil daerah prospek baru di bagian utara P. Peleng, bagian barat P. Banggai, selatan P. Banggai-Taliabu, barat dan timur P. Sulabesi. Daerah prospek tersebut tercermin dari daerah pusat cekungan dengan bentuk morfologi rendahan pada data gaya berat dan prospek perangkap (leads) pada data seismik di bagian barat sekitar Teluk Tolo. Hasil analisis kimia batuan sumber pada Diagram Tmax vs Indeks Hidrogen menunjukkan kualitas kerogen tipe III dan pada Diagram Indeks Oksigen vs Indeks Hidrogen menunjukkan tipe II gas prone, sehingga memberikan gambaran bahwa daerah ini berpotensi mengandung gas. Kualitas gas tersebut termasuk dalam kategori belum matang sampai matang. Kata kunci : geology kelautan, model anomali graviti, perangkap, batuan induk, kualitas hidrokarbon, Cekungan Banggai-Sula